Electrochemical Synthesis of 3-Sulfonylindoles via Annulation of o-Alkynylanilines with Sodium Sulfinates - Jiang, Ping; Liu, Rui; Meng, Xiangtai; Zheng, Binnan; Zheng, Yu; Huang, Shenlin (Synthesis, 2023)
An electrochemical method to synthesize 3-sulfonylindoles from o-alkynylanilines and sodium sulfinates is disclosed. Featuring external oxidant-free, transition metal-free, and mild conditions, this sustainable approach tolerates a wide range of functional groups. Mechanistic studies are presented, revealing that (E)-bis(sulfonyl)stilbenes appear to be the key intermediates in this transformation.
Keywords: organic electrochemistry; indoles; 3-sulfonylindoles; oxidation; sodium sulfinates; alkynylanilines